An Unconventional Approach Considering Flexor Spasticity and Flexion Synergies of the Upper Extremity Following a Stroke: A Randomized Double-blind Pilot Study - Young Hyoun Rha; Keun Hee Lee; Jun Bum Shin; Kang Hui Park; Byung Sun Kim; Jae Chan Ha (Korean Research Society of Physical Therapy, 2022)
Background: Although various conventional approaches have been employed to reduce spasticity in neurological rehabilitation, only a few studies have shown scientific evidence for its effectiveness. Thus, we introduced a different concept (Ueda method) of rehabilitation therapy that can complement the limitations of conventional therapy.Objects: This study aimed to investigate the immediate effects of the application of the Ueda method on patients with spasticity after stroke via an electrophysiological study.Methods: We conducted a randomized double-blind pilot study in two rehabilitation hos-pitals involving 30 stroke patients who were randomly allocated to the Ueda (n = 15) and convention (n = 15) groups. Electromyographic data of six examined muscles in both upper extremities of all patients were recorded. The A-ApA index and activation ratios of upper extremity muscles were evaluated and compared between the groups to confirm post-inter-vention changes in upper-extremity flexor spasticity and flexion synergies. Repeated-measures analysis of variance was conducted to confirm the therapeutic effect (2 × 2) as a function of group (Ueda vs. convention) and time (pre-/post-intervention) on all outcome measures (p < 0.05).Results: In the Ueda group, the mean A-ApA index values differed significantly before and af-ter the intervention (p = 0.041), indicating a weak evidence level; however, the effect size was medium (d = -0.503). The interaction effects of the A-ApA index between the Ueda and con-vention groups and between pre-intervention and post-intervention stages were significant (p = 0.012). The effect size was large (np2 = 0.220). In the Ueda group, the activation ratios of the anterior deltoid fiber significantly decreased after the intervention in all reaching tasks.Conclusion: The Ueda method reduces upper-extremity flexor spasticity and changes its synergy in stroke patients and should be considered a rehabilitation therapy for spastic stroke patients.